Evolution and roles of cytokinin genes in angiosperms 1: Do ancient IPTs play housekeeping while non-ancient IPTs play regulatory roles?. (1st March 2020) - Wang, Xiaojing; Lin, Shanshan; Liu, Decai; Gan, Lijun; McAvoy, Richard; Ding, Jing; Li, Yi
Abstract: Isopentenyltransferase (IPT) genes, including those encoding ATP/ADP-IPT s and tRNA-IPT s, control the rate-limiting steps of the biosynthesis of N 6 -(Δ 2 -isopentenyl)adenine (iP)-type and trans -zeatin ( t Z)-type cytokinins and cis -zeatin ( c Z)-type cytokinins, respectively. However, the evolution and roles of these IPT s in angiosperms are not well understood. Here, we report comprehensive analyses of the origins, evolution, expression patterns, and possible roles of ATP/ADP-IPTs and tRNA-IPT s in angiosperms. We found that Class I and II tRNA-IPT s likely coexisted in the last common ancestor of eukaryotes, while ATP/ADP-IPT s likely originated from a Class II tRNA-IPT before the divergence of angiosperms. tRNA-IPT s are conservatively retained as 2–3 copies, but ATP/ADP-IPT s exhibit considerable expansion and diversification. Additionally, tRNA-IPT s are constitutively expressed throughout the plant, whereas the expression of ATP/ADP - IPT s is tissue-specific and rapidly downregulated by abiotic stresses. Furthermore, previous studies and our present study indicate that ATP/ADP - IPT s and their products, iPs/ t Zs, may regulate responses to environmental stresses and organ development in angiosperms. We therefore hypothesize that tRNA-IPT s and the associated c Zs play a housekeeping role, whereas ATP/ADP-IPT s and the associated iP/ t Z-type cytokinins play regulatory roles in organ development and stress responses in angiosperms, which echoes the conclusions and hypothesis presented in the accompanying study by Wang, X. et al Evolution and roles of cytokinin genes in angiosperms 2: Do ancient CKXs play housekeeping roles while non-ancient CKXs play regulatory roles? Hortic Res https://doi.org/10.1038/s41438-020-0246-z .